Heat transfer enhancement of water-based highly crumpled few-layer graphene nanofluids - Amiri, A.; Ahmadi, G.; Shanbedi, M.; Etemadi, M.; Zubir, M.N.M.; Chew, B.T.; Kazi, S.N. (Royal Society of Chemistry, 2016)
Backward-facing step heat transfer of transitional and turbulent flows occurs in many industrial applications. The heat transfer performances of different multiphase working fluids over a backward-facing step in the transitional and turbulent flow regimes, however, have not been fully investigated experimentally. Recently, highly crumpled few-layer graphene (HCFLG) with a high surface area has been introduced as a promising additive for preparing nanofluids for high performance heat transfer applications. In this work, the heat transfer properties of the HCFLG nanofluids were studied experimentally. The HCFLG was prepared by exfoliation of graphite in the presence of liquid-phase using microwave-assisted methods, which was shown to be industrially-scalable, cost-effective, and simple. Then the HCFLG was used for fabricating a new class of water-based graphene nanofluid for use in large-scale heat transfer equipment. The prepared water-based HCFLG nanofluids were shown to be stable with less than 2% sedimentation after 30 days. In addition, the measured thermophysical properties indicated that the water-based HCFLG nanofluids have huge potential for high performance heat transfer applications. Finally, the water-based HCFLG nanofluids were shown to be significantly more effective in the duct with a backward-facing step in terms of overall thermal performance including the local Nusselt number (Nu), convective heat transfer coefficient, performance index, pumping power, and rheological properties such as effective viscosity in comparison to distilled water.